Cloud Computing: Models, Issues and Challenges - R, Komala; BV, Pranavi (International Journal of Computer Sciences and Engineering, 2021)
In modern days, Cloud storage service is being increased tremendously for storing the data. Cloud computing is the new development in the IT industry now a days. The main advantage of cloud storage service is that the data can be downloaded from any location and at any time without any limitation. But, data security is considered as main issue in the cloud computing. Mainly sharing of resources will have major issue in the data security. Cloud deployment models, delivery models are High level cloud architecture is being explained with its four levels. Various challenges and security issues in this cloud computing has been stated clearly in this paper.